PENGARUH DISIPLIN KERJA, STRES KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT.POS INDONESIA (PERSERO) RENDANG - Ni Komang Irma Bapriani; Anak Agung Putu Agung; I Nengah Sudja (VALUES, 2023)
This study aims to test and determine the effect of work discipline, work stress and physical work environment on employee performance at PT. Pos Indonesia (Persero) Rendang. The independent variable (X) is work discipline, work stress, and work environment while the bond variable (Y) in this study is employee performance. The sample in this study were 50 employees. Sampling using saturated sampling. This study uses the classical assumption test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, analysis of the coefficient of determination, simultaneous significance test (F), and partial test (t). The results showed that the variables of work discipline, work stress and work environment partially had a positive and significant effect on employee performance at PT. INDONESIAN POST.